EFEKTIVITAS DAN TANTANGAN E-LEARNING TAHSIN DAN TAFSIR: INTEGRASI AL DAN PERILAKU GEN Z - Loka, Dara Puspita; Bashori, Bashori (Universitas Tanjungpura, 2025)
The digital transformation of Islamic education has opened new avenues for Qur